Comparative study of ferrocement panels reinforced with galvanized iron and polypropylene meshes. (20th June 2019) - Mughal, Ubaid Ahmad; Saleem, Muhammad Azhar; Abbas, Safeer
Abstract: Ferrocement panels reinforced with galvanized iron (GI) mesh have been in use historically, however in the regions where humidity levels are high the GI mesh tends to corrode, leading to reduced service life. Polypropylene (PP) mesh, having rust free character, may serve as an alternative to GI mesh. This paper presents an experimental study intended to compare the flexural and compressive strength behavior of ferrocement panels reinforced with GI and PP meshes. A total of 32 rectangular ferrocement panels were tested: 16 in flexure and 16 in compression. Out of 16 panels tested in flexure, 8 were reinforced with GI mesh and 8 with PP mesh. Similarly, 8 GI and PP mesh panels each were test in compression. The specimens tested in flexure were simply supported on two short edges and were tested under four point bending. The specimens tested in compression were hinged at both ends. The parameters investigated include thickness of panels, volume fraction and the material of the mesh. All the GI mesh panels outclassed the PP mesh panels both in flexure and compression strength. However, PP mesh panels exhibited better ductility properties as compared to GI mesh panels. The load carrying capacity of both GI and PP mesh panels increased with the increase in panel thickness and number of mesh layers.